Removal of 2-chlorophenol from aqueous system by adsorption over maize husk - Md. M.H. Mondol; Md. I. Khalil; Md. N. Amin (Desalination and Water Treatment)
In this work, maize husk (MH) was utilized as an adsorbent to eliminate 2-chlorophenol (2-CP) from wastewater. The effects of several factors such as adsorbent dose, time, solution concentration, absorbent size, pH, and temperature were investigated. The results showed that within 2 h adsorption equilibrium was achieved. The adsorption equilibrium data for 2-CP-sorbent systems were fitted well with the Freundlich and Langmuir models within the investigated concentration range. In addition, Kinetic study revealed that diffusion was the major rate-controlling stage; and the adsorption process could be explained by both first- and second-order rate equations. The adsorption process was found to be exothermic in nature, and the adsorption mechanism might be explained by hydrogen and electrostatic force of interaction between the functional group of MH and 2-CP, along with some contribution of Van der Waals force. Therefore, MH might have the potential for use as an adsorbent in removing 2-CP from water and wastewater.